THE JOURNAL OF THE RESEARCH HOW TO DEVELOP THE STUDENTS’ ABILITY IN ACTIVE SKILL - Rohasi Naibaho (BAHAS, 2019)
SMP Negeri 2 SilimaPunga-Punga, is one of unit institution of education, beneath Ministry of National education that must be developed is quality, especially in English lesson. The teacher much develop their ability in teaching. The teacher must be creative, do not apply menotoneus teacher thecniques and methods. Start the lesson by doing some elicitation, brainstorming, etc. The English teacher have some strategies to make students know the four skills easily by easing some methods as in this journal, it is written in conversation skill by using audio visual as to Television and Cassettes. The intentions from using those methods to make students know the skills of English Easily. The active skills is necessary so the students can practice English Language during process of learning, The students are active and the teachers have to have the stimulus to make the students have the strategies how to answer what the teacher needs in the classroom. Besides, the students are motivated to speak English by using visual method. Their ability in spoken will be developed by using that method. The improve of quality and the results of teaching and the students’ ability spoken, can be seen in three indicators. First, the students’ enthusiastic. Second, the students’ serious and the third the students, ability in conversation skills, in the research, those skill can be developed by students. It Shows that media is important to teach English Lesson. Kata Kunci : Active Skill